2018
DOI: 10.1016/j.anr.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effects of Social Support and a Grateful Disposition on the Relationship between Life Stress and Anger in Korean Nursing Students

Abstract: Based on this study's results, enhancing social support and grateful disposition could help nursing students who experience anger resulting from life stress to manage their anger effectively. This finding suggests that, as specific strategies for anger management, nursing educators should encourage nursing students to use sources of social support and to engage in various gratitude activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…Family support has consistently been identified as playing an important role in academic persistence (Abukari, 2010 ; Nelson, 2019 ; Sosu & Pheunpha, 2019 ; Theodore et al, 2017 ), while support derived from peers and support groups is associated with positive academic outcomes (Kim et al, 2017 ; Li et al, 2018a , b ), including enhancing understanding of course materials and clarifying difficult concepts (Collins et al, 2010 ; Gallop & Bastien, 2016 ; Masserini & Bini, 2021 ). In terms of other sources of support, while students may access support from academic staff to a lesser extent than that from other sources (Blair, 2017 ; Casapulla et al, 2020 ; Reeve et al, 2013 ), these relationships are found to be important for both wellbeing and transition to university (Cage et al, 2021 ; Jun et al, 2018 ; Maymon et al, 2019 ; Meehan & Howells, 2017 ; Reeve et al, 2013 ). Research has identified that certain programmes due to teaching methods and small group classes may lead to greater peer social support (Jun et al, 2018 ).…”
Section: Social Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…Family support has consistently been identified as playing an important role in academic persistence (Abukari, 2010 ; Nelson, 2019 ; Sosu & Pheunpha, 2019 ; Theodore et al, 2017 ), while support derived from peers and support groups is associated with positive academic outcomes (Kim et al, 2017 ; Li et al, 2018a , b ), including enhancing understanding of course materials and clarifying difficult concepts (Collins et al, 2010 ; Gallop & Bastien, 2016 ; Masserini & Bini, 2021 ). In terms of other sources of support, while students may access support from academic staff to a lesser extent than that from other sources (Blair, 2017 ; Casapulla et al, 2020 ; Reeve et al, 2013 ), these relationships are found to be important for both wellbeing and transition to university (Cage et al, 2021 ; Jun et al, 2018 ; Maymon et al, 2019 ; Meehan & Howells, 2017 ; Reeve et al, 2013 ). Research has identified that certain programmes due to teaching methods and small group classes may lead to greater peer social support (Jun et al, 2018 ).…”
Section: Social Supportmentioning
confidence: 99%
“…In terms of other sources of support, while students may access support from academic staff to a lesser extent than that from other sources (Blair, 2017 ; Casapulla et al, 2020 ; Reeve et al, 2013 ), these relationships are found to be important for both wellbeing and transition to university (Cage et al, 2021 ; Jun et al, 2018 ; Maymon et al, 2019 ; Meehan & Howells, 2017 ; Reeve et al, 2013 ). Research has identified that certain programmes due to teaching methods and small group classes may lead to greater peer social support (Jun et al, 2018 ). The current study included students from a range of disciplines to allow consideration of students from a range of disciplines, with different levels of social support.…”
Section: Social Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Social support has been reported to play a key role in alleviating physical and psychological health problems due to the stress of daily life and in promoting psychological wellbeing [ 22 , 23 ]. Social support has been reported as the most important predictor of burden in family members of patients with cancer [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering this, the present study developed an ASCP that differs from existing programs by focusing on increasing understanding of the emotional, cognitive, and behavioral aspects of anger, based on the cognitive behavioral model, and on strengthening coping behaviors for controlling anger effectively, based on the positive psychological model as an extracurricular program. Moreover, the effects of developed ASCP were assessed by grateful disposition reported to have protective effects against anger [19] and a risk factor, i.e., depression for anger expression [20], as well as trait anger and anger expression style. The aim of this study is to investigate the effects of an anger self-control program on trait anger, anger expression style, grateful disposition, and depression among nursing students.…”
Section: Introductionmentioning
confidence: 99%